About possibility of measurement of single-photon spectra under condition of multiple photon generation; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 173, iss. 1-2 : Radiation from Relativistic Electrons in Periodic Structures - Bochek G. L.; Kalinin B. N.; Kulibaba V. I.; Lapko V. P.; Maslov N. I.; Naumenko G. A. Gennadiy Andreevich; Ovchinnik V. D.; Potylitsyn A. P. Alexander Petrovich; Schramenko B. I.; Sharafutdinov A. V.; Starodubtsev A. F.; Vnukov I. E. (2001, 2001)
Title screen